The Influence Of Loan Eligibility And Ability To Repay On The Level Of Bad Credit In Cooperatives Cu. Our Hopes Will Before - Simanungkalit, Rakelina Nainti; Rangkuti, Sahnan; Firah, Al (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
The aim of this research is to determine the influence of loan eligibility and repayment capacity on CU bad credit levels. Harapan Kita Belawan. The data collection techniques for this research are observation, questionnaires and documentation studies with data analysis techniques, namely multiple linear regression analysis. The conclusion in this research is that there is the influence of loan eligibility partially on the level of bad credit at CU. Harapan Kita Belawan, this is known as the t valuecount as big as 4,818 which compared to the t table of 1.66055 then 4.818 > 1.66055 which means the loan eligibility variable has a real (significant) and positive influence on the bad credit level variable. Besides that there is an influence on the ability to pay partially on the level of bad credit at CU. Harapan Kita Belawan, this is known as the tcount amounting to 18,086 Which compared to ttable  is 1.66055 then 18.086 > 1.66055 which means the ability to pay variable has a real (significant) and positive influence on the bad credit level variable. Next there is the influence of loan eligibility and ability to pay simultaneously on the level of bad credit at the CU Cooperative. Our Hope Against this is known from the F valuecount = 200.015 which is compared to Ftable of 3.09 then 200.015 > 3.09 which means the loan eligibility variable and ability to pay simultaneously has a real (significant) or positive influence on the variable level of bad credit.